Mengungkap Kebijaksanaan Ilmiah Al-Qur’an : Studi Kasus Tafsir ‘Ilmi Ayat-ayat terkait Sumber Daya Alam dan Lingkungan di Banten - Raudotul Jannah; Fitriyah Handayani; Putri Hudani Nabila; M Farih Alawi; Andi Rosa (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
This article explores the Qur'anic perspective on contemporary ecological issues, particularly in the context of the environmental crisis in Banten Province, Indonesia. Using a thematic and tafsir ilmi (interpretation) approach, this qualitative literature-based study analyzes Qur'anic verses related to nature and resources, such as QS. Al-A'raf: 56, QS. Al-Baqarah: 60, QS. An-Nahl: 10–11, and QS. Al-Anbiya: 30. This article integrates the values ​​of revelation with modern ecological thought to understand ecological responsibility in Islam and its relevance to local environmental challenges, including the clean water crisis caused by deforestation and pollution. This study also highlights local initiatives such as the Banten Bebersih movement as an example of the implementation of Qur'anic values ​​in environmental conservation efforts. The research findings show that the Qur'an not only prohibits environmental degradation and emphasizes the importance of balance (mizan), but also provides theological and ethical foundations for sustainable natural resource management and equitable distribution. This article concludes that the integration of Islamic studies and environmental science offers a comprehensive and relevant ecological paradigm to address environmental challenges in the modern era.